L’imprevedibile virtù dell’ambiguità. Il caso Fargo nel panorama della serialità televisiva di ultima generazione - Attanasio, Gianlorenzo (Status Quaestionis, 2024)
This study is divided into two sections, a first one of a more theoretical nature in which an attempt is made to introduce the concept of television seriality and to cast it within a theory of media that looks at the mechanisms of production and consumption, but above all at the possibilities of writing as a creative space in which complexity and originality are produced; in the second part, on the other hand, the series Fargo is analyzed as a model of a complex seriality, based on writing that repudiates the stereotype, and indeed tries to make it its punctum, overthrowing it insofar as it systematically sets out to disregard the viewer's expectations.